Marketing Meets Money: The Role of Marketing Mix, Financial Literacy, and Brand Trust in Shaping Retail Investors' Decisions on Digital Investment Platforms in Indonesia - Adine Setya Wardhani; Widaningsih (Yayasan Pendidikan Belajar Berdikari, 2026)
Financial decision-making has traditionally been examined through the lens of economic rationality and behavioral finance, while the persuasive role of marketing has received comparatively little attention in finance research. This study bridges the finance and marketing literatures by examining how marketing mix, financial literacy, and brand trust jointly influence retail investors' decisions to invest through digital investment platforms in Indonesia. Using a quantitative explanatory design, data were collected from 250 active users of fintech investment applications through an online structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that marketing mix and brand trust significantly and positively influence investment intention, that brand trust partially mediates the effect of marketing mix on investment intention, and that financial literacy significantly moderates the relationship between investment intention and actual investment decisions by strengthening the conversion of intention into action. These findings indicate that investment decisions in the digital era are not purely rational financial calculations but are also shaped by marketing-driven perceptions of value and credibility. The study contributes to the emerging literature at the intersection of behavioral finance and marketing management, and offers practical guidance for fintech platforms in designing marketing communication strategies that build long-term investor trust rather than relying solely on short-term promotional incentives.